Global media product and construction of “Japanese identity”: a case study of anime on Malaysian Television - Juliana Abdul Wahab; Mustafa K Anuar; Farhani (Universiti Kebangsaan Malaysian, 2012)
Japanese animation or, as it is popularly known, anime appears to be the most celebrated Asian television product around the globe today. Anime was first created in 1917 and developed well into the 1970’s in Japan. By the 1990’s anime series, such as Dragon Ball, Pokemon, and Sailormoon became worldwide successes (Patten: 2009). By the year 2000, the proliferation of Japanese animation in the global market is beyond imagination. Current global response and market trend suggest that the anime industry is indeed a significant contribution to the economic growth of Japan. Proliferation of Japanese programmes in Malaysia became prominent in the 1980’s where more Japanese dramas and anime were used to fill in the time slot. The fact that the percentage of imports of animation programme from the west had decreased in the recent years suggests that Japanese anime has started to claim a steady position in Malaysian television industry. It is in this larger context that this study aims to understand how “Japaneseness’ has been negotiated in representing Japan unique identity in anime through critical content analysis of selected anime programmes available on Malaysia television.